Self-assertion in Selected Plays by Ibsen (Journal of Hama University, 2019)
This study aims at discussing the theme of self-assertion in some plays by Henrik Ibsen; A Doll’s House, Ghosts, A Public Enemy, and When We Dead Awaken. The study proceeds to explore the characters’ major motives to assert their own sense of selfhood which takes the form of self-esteem, and the quest for social or political status. It also, shows the characters’ awareness of their failure that leads to disappointment, frustration, madness, introversion, alienation, or suicide. The quest for self-assertion appears in the most famous characters of the above-mentioned plays. Nora in A Doll’s House discovers the causes of her confused personality, so she decides to find out a solution that helps her understand the truths about herself and the world. Accordingly, she leaves her house to assert her own self independently. Mrs. Alving in Ghosts breaks her society laws in an attempt to prove her own thoughts. However, she fails because of her past. Doctor Stockmann struggles against corrupt bureaucrats and strives to assert his position so as to save his own community. Professor Rubek renounces his true love for the sake of Art, thinking that he finds his true personality in Art. Later on, he discovers that his selfish way of proving his artistic value has been complete blindness which leads to self-destruction.